Prospects of Production of Ecologically Clean Agricultural Products in the Transboundary Territories of the Great Altai - GLOTKO, Andrei Vladimirovich; SYCHEVA, Irina Nikolaevna; PERMYAKOVA, Elena Sergeyevna; DANILCHIK, Tatyana Leonovna; USENKO, Varvara Dmitrievna (Journal of Environmental Management and Tourism; Vol 8 No 7 (2017): JEMT Volume VIII Issue 7(23) Winter 2017DO - 10.14505//jemt.v8.7(23).05, 2018)
A scientific basis for agriculture based on production of organic products has been developed. The concept and the management mechanism for the agriculture development aimed at organic production have been generated. The importance of production and consumption of ecologically clean products has been confirmed by the analysis of efficiency of the innovative entrepreneurship development in agriculture. The organizational mechanism for strategic development of maral breeding in the Altai Territory and the Republic of Altai has been improved and tested, which in contrast to the existing ones has been complemented by the scenario approach to planning and forecasting. The main stages of production of ecologically clean maral products in the Altai Territory and the Republic of Altai have been given. The proposals for strategic development of regional maral breeding in the Altai Territory and the Republic of Altai have been presented. The most probable scenario for the maral breeding development on the basis of a stage-by-stage method has been proposed, and the normative model for the state of the maral breeding industry has been developed.